The Response of the Ozone Layer to Quadrupled CO2 Concentrations: Implications for Climate - Chiodo, Gabriel; id_orcid:0 000-0002-8079-6314; Polvani, Lorenzo M. (American Meteorological Society, 2019)
The quantification of the climate impacts exerted by stratospheric ozone changes in abrupt 4 × CO2 forcing experiments is an important step in assessing the role of the ozone layer in the climate system. Here, we build on our previous work on the change of the ozone layer under 4 × CO2 and examine the effects of ozone changes on the climate response to 4 × CO2, using the Whole Atmosphere Community Climate Model. We show that the global-mean radiative perturbation induced by the ozone changes under 4 × CO2 is small, due to nearly total cancellation between high and low latitudes, and between longwave and shortwave fluxes. Consistent with the small global-mean radiative perturbation, the effect of ozone changes on the global-mean surface temperature response to 4 × CO2 is negligible. However, changes in the ozone layer due to 4 × CO2 have a considerable impact on the tropospheric circulation. During boreal winter, we find significant ozone-induced tropospheric circulation responses in both hemispheres. In particular, ozone changes cause an equatorward shift of the North Atlantic jet, cooling over Eurasia, and drying over northern Europe. The ozone signals generally oppose the direct effects of increased CO2 levels and are robust across the range of ozone changes imposed in this study. Our results demonstrate that stratospheric ozone changes play a considerable role in shaping the atmospheric circulation response to CO2 forcing in both hemispheres and should be accounted for in climate sensitivity studies. ISSN:0894-8755 ISSN:1520-0442